Analysis Of ZDS and LCYb Enzyme Coding Gene Related To Beta Carotene Bioshynthesis in Cassava (Manihot esculenta Crantz) using Reverse transcription PCR (RT-PCR) - Jihan Rezi Okanti; Dwi Hilda Putri; Ahmad Fathoni (Bioscience, 2020)
This study aims to determine variations in the expression of ZDS and LCYb enzymes encoding several types of yellow tubers. Cassava used, namely Carvita 25, Nangka and Mentega 2 (yellow bulb) and Menti (white bulb) were used as controls. The target enzyme coding genes (ZDS and LCYb) in cassava were identified in an online database, Phytozome using the BLAST method. Design and primary analysis for the target genes was carried out using online software, OligoAnalyzer and PCR. The expression of the target enzyme coding gene was analyzed using the Reverse Transcription PCR (RT-PCR) method. The BLAST results in the cassava genome in the Phytozome database showed that the enzymes ZDS and LCYb in cassava were encoded by two genes. The primary optimization results showed the primary annealing temperature for the LCYb enzyme coding gene was 55 ° C. The ZDS primers were not amplified after several replications, so that only the LCYb enzyme coding gene was selected for qualitative gene expression analysis using RT-PCR. A positive control in the analysis of gene expression is the housekeeping gene, PP2A. Electrophoresis results of PCR products (RT-PCR) showed negative results (no DNA bands were detected) in all samples from both yellow and white tuber samples and its housekeeping gene. This is possible from the low quality of RNA used in cDNA synthesis.